Offence of Failure to Report a Work-related Accident in Poland - Katarzyna Banasik (Societas et Iurisprudentia, 2019)
This paper focuses on the criminal offence of failure to report a work-related accident. The offence in question has been defined under the Article 221 of the Polish Criminal Code. The author starts by considering what kind of interest is protected against the offence in question and continues with a detailed analysis of the offender and the objective element of the offence. The author also explains the mental element of this crime and analyses the relevant provisions of the Polish Criminal Code, Labour Code and other legal acts concerning labour law and social insurance law.